Hamlet - Shakespeare, William (Don Mills, Canada Academic Press Canada, 1961)
Probably the most famous play in the English language, Hamlet transcends the revenge tradition and explores the nature of man. Learning that his father has been killed by Claudius, his uncle, Hamlets only honourable course of action is revenge. But Hamlets nature tends not towards action but reflection and in his incapacity to act lies the seed of his own destruction.
Keywords: Literature